Personnel supply and demand for civil aviators in Taiwan - Lin, Chin-Tsai; Juan, Pin-Ju (Transport, 2007)
This work was based on data from 2000–2005 provided by the Civil Aeronautics Administration Ministry of Transportation and Communications, and applied the GM (1,1) model of Grey theory to forecast annual demand and supply for civil aviators in Taiwan. This work adopted a five‐year moving average to calculate the transition probability for civil aviators in Taiwan from 2006–2010 considering various levels of seniority. The study results provide a valuable reference for the relevant authorities in identifying the manpower policies of Taiwanese airlines.First Published Online: 27 Oct 2010